HUMA BETANG SEBAGAI BUDAYA TANDINGAN: Relevansi Teologi Kontekstual Bagi Gereja Di Kalimantan Tengah - Susilawati Susilawati; Sofiya Cristine; Yolanda Meliyani BR Surbakti; Sarmauli Sarmauli (Adisam Publisher, 2025)
Huma Betang is a cultural symbol of the Dayak Ngaju people in Central Kalimantan, representing not only a physical dwelling but also a worldview grounded in togetherness, tolerance, justice, deliberation, and simplicity. Within contextual theology, Huma Betang serves as a countercultural model that challenges the growing tide of globalization and modernity marked by individualism, materialism, and competition. This study aims to explore the relevance of Huma Betang’s values for church life in Central Kalimantan, particularly in the practice of contextual theology. Using a descriptive-qualitative method through theological and cultural literature analysis, the study reveals that Huma Betang’s values align with Gospel principles and can serve as the foundation for a contextual and transformative church community. A church rooted in Huma Betang’s ethos becomes an alternative community that resists dominant culture while embodying love, social justice, and ecological spirituality.